Pembuatan Website Wiki Bangunan Bersejarah Indonesia - Ferdi Limoang; Liliana Liliana; Kristo Radion Purba (Jurnal Infra, 2016)
Indonesia is one of the countries that has many historic buildings which are recognized by the world. Some examples of notable historic building is the Temple of Borobudur, prambanan Temple, the Fort remains by Netherlands and Japan, and others. In addition to the large number of historic buildings, there is no dedicated media that truly embody information on historic buildings. Thus, needed a site that could be a medium where people can share information about the historic buildings at once into a medium of communication between users of the site in response to the information. The system has the capability to provide and accommodate existing information and can provide a medium of communication between users. The data on the system is derived from the user and can be accessed by users as well. The site will be controlled by Admin, where Admins on duty to supervise the site.Overall this system can help the user in providing and seeking information about historic building in Indonesia and also can be a medium of communication between users in response to the information.